Widespread declining in vegetation climate sensitivity across Central Asia - Jiang, Ping; Zhang, Yue; Wang, Tuanhui; Guzainuer, Keremu (Frontiers in Environmental Science, 2025)
As the world’s largest azonal arid region, Central Asia harbors fragile ecosystems that are highly sensitive to shifts in climate patterns. However, the spatiotemporal dynamics of vegetation sensitivity and their underlying drivers in this region remain poorly understood. Here, we assessed vegetation responses to climate variability from 1982 to 2022 using the longest available time series of vegetation indices and the Vegetation Sensitivity Index (VSI) metric. Results revealed high VSI (>50) in humid-region forests and shrubs as well as in semi-arid rainfed croplands, while arid zones generally exhibited low VSI values (<30). Relationship between VSI and aridity was observed across most vegetation types, excluding rainfed agriculture and sparse vegetation. Temporally, the VSI in Central Asia showed a clear declining trend, with the rate of decrease accelerating after 1995 from −0.274 to −0.476. Spatially, approximately 82% of vegetated areas showed declining VSI trends over the past four decades, with 49% exhibiting statistically significant decreases. Temperature and atmospheric CO2 concentration were identified as primary drivers of VSI trends, with warming promoting and CO2 largely suppressing vegetation sensitivity. Water availability—including precipitation and soil moisture—also exerted notable regulatory influence on VSI dynamics. These findings address critical knowledge gaps in the understanding of vegetation–climate interactions in Central Asia and offer valuable insights for projecting ecosystem responses under future climate scenarios.